11(z+2)=2(z+6)-13

Simple and best practice solution for 11(z+2)=2(z+6)-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(z+2)=2(z+6)-13 equation:



11(z+2)=2(z+6)-13
We move all terms to the left:
11(z+2)-(2(z+6)-13)=0
We multiply parentheses
11z-(2(z+6)-13)+22=0
We calculate terms in parentheses: -(2(z+6)-13), so:
2(z+6)-13
We multiply parentheses
2z+12-13
We add all the numbers together, and all the variables
2z-1
Back to the equation:
-(2z-1)
We get rid of parentheses
11z-2z+1+22=0
We add all the numbers together, and all the variables
9z+23=0
We move all terms containing z to the left, all other terms to the right
9z=-23
z=-23/9
z=-2+5/9

See similar equations:

| √(x-1)=81 | | 3/2(16n)+3=24n | | $101.00=2h | | -4k+3.6=8.8 | | 51÷4=x | | 2x-3(41-4x)=3 | | (2m/9)+(3m/14)=1 | | 1/2a=1/6a+3 | | 8/9(y-14=-6 | | 3(x-5)=6x+10 | | -8+t=-2 | | -2(7k-3=-92 | | -2(3-7v)=-5v+13 | | 21=3v+15-6v | | 45+2x=55 | | 8(n+6)-6n=-(-6+4n) | | 30+3x=40 | | x+1/2+x+6/9=1 | | 2a-8-5a=10 | | 2n+16=56 | | 8-(3b-5)=-5+2(b+1) | | 2,380+175.75w=5,367.75 | | 0.714285714286=1/x | | 2.3x-2=2 | | 0.714285714286x=22 | | 3.25x(-0.4)=0 | | 6(7+2p)=3(p | | -7.8d=-1.56 | | 400+25x=68+25x | | 9x+22=-15 | | -9w+1=7-7w | | ⅓(m+21)+⅔m=-2 |

Equations solver categories